Cannabinoid type-1 receptors in CaMKII neurons drive impulsivity in pathological eating behavior - Elena Martin-Garcia; Laura Domingo-Rodriguez; Beat Lutz; Rafael Maldonado; Inigo Ruiz de Azua (Molecular Metabolism, 2025)
Objectives: Overconsumption of palatable food and energy accumulation are evolutionary mechanisms of survival when food is scarce. These innate mechanisms becom detrimental in obesogenic environment promoting obesity and related comorbidities, including mood disorders. This study aims at elucidating the role of the endocannabinoid system in energy accumulation and hedonic feeding. Methods: We applied a genetic strategy to reconstitute cannabinoid type-1 receptor (CB1) expression at functional levels specifically in CaMKII+ neurons (CaMKII-CB1-RS) and adipocytes (Ati-CB1-RS), respectively, in a CB1 deficient background. Results: Rescued CB1 expression in CaMKII+ neurons, but not in adipocytes, promotes feeding behavior, leading to fasting-induced hyperphagia, increased motivation, and impulsivity to palatable food seeking. In a diet-induced obesity model, CB1 re-expression in CaMKII+ neurons, but not in adipocytes, compared to complete CB1 deficiency, was sufficient to largely restore weight gain, food intake without any effect on glucose intolerance associated with high-fat diet consumption. In a model of glucocorticoid-mediated metabolic syndrome, CaMKII-CB1-RS mice showed all metabolic alterations linked to the human metabolic syndrome except of glucose intolerance. In a binge-eating model mimicking human pathological feeding, CaMKII-CB1-RS mice showed increased seeking and compulsive behavior to palatable food, suggesting crucial roles in foraging and an enhanced susceptibility to addictive-like eating behaviors. Importantly, other contingent behaviors, including increased cognitive flexibility and reduced anxiety-like behaviors, but not depressive-like behaviors, were also observed. Conclusions: CB1 in CaMKII+ neurons is instrumental in feeding behavior and energy storage under physiological conditions. The exposure to risk factors (hypercaloric diet, glucocorticoid dysregulation) leads to obesity, metabolic syndrome, binge-eating and food addiction.